LEGAL SUPPORT OF THE FORMATION OF A MODERN STRATEGIC PLANNING SYSTEM IN RUSSIA - N. M. Mukhetdinova (Финансы: теория и практика)
The establishment of a modern state strategic planning system conformant to current realities is a matter of vital importance for Russia. During the transition to market economy in the 1990s the centralized planning system was abandoned, the methodology and technologies of development and implementation of long-and mid-term plans were lost as well. Meanwhile, quite a number of foreign countries based on the Soviet planning experience are widely using government regulation of the economy, particularly centralized forecasting, planning and programming of socio-economic processes, along with market control tools. In the recent decades, usage of indicative planning methods has transformed into application of programming methods in steering the economy. The article analyzes the draft law «Strategic planning in the Russian Federation» ready for the 2nd hearing in the State Duma,which creates a legal frameworkfor emergence of an appropriate planning system in Russia.The analysis reviews objectives targeted by the draft law as well as new planning documents including state programs and the long-term budget strategy introduced to ensure the financial realization of the strategic development goals set by the state. The article focuses on the program management and program budget issues identified during the hearing of the draft federal budget for the 2014-2016. The author considers such an important aspect, spotted during the draft law preparation, as ensuring the draft law consistency with the Budget Code of Russia (including practical ways to maintain this). Issues to be solved by amendments after the draft law is adopted have been formulated.